Computer vision coupled with laser backscattering for nondestructive colour evaluation of papaya during drying - Udomkun, Patchimaporn; Nagle, M.; Argyropoulos, D.; Wiredu, A.N.; Mahayothee, B.; Müller, J. (Springer, 2017)
Colour change is a common physical phenomenon observed during drying, which need to be controlled since it directly affects consumer acceptance of dried products. This study aimed to investigate the feasibility of using computer vision, combined with laser light backscattering analysis at 650 nm in order to predict colour changes of papaya during drying. The results revealed that each image-processing factor obtained can potentially be used to describe every colour attribute change, except for chroma value. The multivariate correlations of measured backscattering parameters as well as the digital image properties were found to yield the best fitting for colour validations. Interestingly, the use of computer vision technique coupled with laser backscattering methods provides a reliable tool for quality control based on a rapid, consistent, and nonintrusive method for in-line quality measurement in established fruit drying processes.